2021
DOI: 10.1177/00914150211037657
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Cohesion and Mobility Limitations Among Community-dwelling Older Americans: The Mediating Roles of Depressive Symptoms and Mastery

Abstract: Neighborhood environment plays an important role in late-life health; yet, the social aspect of neighborhood environment and its impact on mobility limitations have rarely been examined. This nonexperimental, cross-sectional study examines the relationship between neighborhood social cohesion and mobility limitations and the potential mediators (i.e., depressive symptoms, mastery) of this relationship. A total of 8,317 Americans aged 65 years and older were selected from the Health and Retirement Study. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…A previous study reported that the overall prevalence of frailty was 9.9% in Chinese older adults [ 30 ].To develop effective prevention of frailty in older adults from the SC perspective, the potential mediating role in the relationship between SC and frailty ought to be understood. Prior work has found that SC can indirectly affect health by reducing the risk of depression [ 31 ]. However, it remains unknown whether the mediating role of depression can be generalized to the relationship between SC and frailty.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that the overall prevalence of frailty was 9.9% in Chinese older adults [ 30 ].To develop effective prevention of frailty in older adults from the SC perspective, the potential mediating role in the relationship between SC and frailty ought to be understood. Prior work has found that SC can indirectly affect health by reducing the risk of depression [ 31 ]. However, it remains unknown whether the mediating role of depression can be generalized to the relationship between SC and frailty.…”
Section: Introductionmentioning
confidence: 99%